The effect of DMDHEU modification on physical and biological properties of parallel strand lumbers - Kurt, Ramazan; Dizman Tomak, Eylem (Elsevier Sci Ltd, 2019)
In this study, the effect of dimethylol dihydroxyethyleneurea (DMDHEU) modification with four different concentration levels on several properties of parallel strand lumbers (PSLs) produced from poplar veneer strands with phenol and melamine formaldehyde adhesives was studied: density, moisture content, water absorption, thickness swelling, dimensional stability, wettability and decay resistance against C. puteana and T. versicolor attacks. Accelareted aging test was conducted in order to evaluate any loss in effectiveness in decay resistance and dimensional stability due to possibility of cleavage of adhesive bonds in lumbers in outdoors. The PSLs produced with modified strands presented higher density and dimensional stability related with their weight gain but lower moisture content, thickness swelling and water absorption than the controls. DMDHEU modification of PSLs was found efficacious in suppressing brown and white rot fungi attacks, but the protective effect was low when lumbers were aged. PSLs manufactured from rotary peeled veneer strands modified with 5% weight gain of DMDHEU and phenol formaldehyde adhesive showed the most promising results for the investigated properties. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Chemical modification; Decay resistance; Dimensional stability; DMDHEU; PSL